Psychological factors of the image of the state in the students’ perception - Karkovska, Ruslana (Journal of Education Culture and Society, 2020)
The article is dedicated to the study of the psychological determination of the state’s image in the students’ perception. The results of empirical research of the infl uence of the students’ adaptation and orientation to their vision of the state are described in the article. The state image in the perception of student youth was analyzed according to the parameters of the state’s accomplishment assessment, the feeling of a sense of belonging to the state, thesense of vision of the state existence and the assessment of the state power as competent, effective, credible, and strong.